The Sociedad Artístico-Fotográfica “Los Treinta”. An example of Bourgeoisie Amateur Photography - Sánchez Vigil, Juan Miguel (Revista General de Información y Documentación, 2022)
Amateur photography societies appeared in Spain in the second half of the 19th century, but encountered major recognition in the first third of the 20th. They were made up of aristocrats, politicians, public servants, military and liberal professionals (lawyers, doctors, architects, professors, journalists, etc.), and their goal was to encourage the practice, spreading and advancement of photography through a variety of activities. They had a three-fold purpose: entertaining, formative and promotional, by means of exhibitions, contests and publications. The aim of this article is to present the Sociedad Artístico- Fotográfica “Los Treinta” and discuss their goals, activities and members. Created in January of 1910, its life was short, until June of 1911, and its list of members included some highly noteworthy authors of the time, such as Santiago Alhassá, Sebastián Castedo, Ramón González, Máximo Orrios, Telesforo Pérez Oliva, José María Álvarez de Toledo, Joaquín Fungairiño and Antonio Prast.
Keywords: Amateur photography; History of Photography; Pictorial Photography; Photographic societies; Sociedad Artístico-Fotográfica Los Treinta.